2019
DOI: 10.1101/2019.12.15.876649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organophosphorus diisopropylfluorophosphate (DFP) intoxication in zebrafish larvae causes behavioral defects, neuronal hyperexcitation and neuronal death

Abstract: 24As key compounds for modern cultivation practices, organophosphorus (OP)-containing pesticides 25 have become an important public health and environmental issues, worldwide, causing millions 26 human intoxications each year. OP poisoning induces cholinergic syndrome, associating 27 irreversible brain damages with epileptic seizures, possibly ending in life-threatening status 28 epilepticus. Existing countermeasures are life-saving, but insufficiently effective to prevent long 29 lasting neuronal consequences… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Perinatal exposure of rats to organophosphorus pesticides alters brain morphometry (Veronesi and Pope, 1990). Similarly, our recent studies have shown that embryos exposed to organophosphorus pesticides showed neurodevelopmental disorders, including altered excitatory/inhibitory synapse balance (Brenet et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Perinatal exposure of rats to organophosphorus pesticides alters brain morphometry (Veronesi and Pope, 1990). Similarly, our recent studies have shown that embryos exposed to organophosphorus pesticides showed neurodevelopmental disorders, including altered excitatory/inhibitory synapse balance (Brenet et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…The percentage of apoptosis in cells of zebrafish larvae is determined [25] using AO stain; a nucleic acid staining dye used to detect early stages of apoptosis. Apoptosis was studied in 96‐h zebrafish larvae using AO staining protocol.…”
Section: Methodsmentioning
confidence: 99%